The Relationship between Health Workers’ Support and Frequency of Visual Inspection with Acetic Acid for Cervical Cancer Early Detection among Childbearing Age Women at Pasir Mulya Health Center - Salsalina Yuniarty G.; Astry Susanti; Reny Siswanti; Helza Risdianti; Tisna Yanti (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Cervical cancer could be prevented through early detection method. Visual Inspection with AceticAcid (VIA) is one of common and simple procedures to screen early stage of cervical cancer. Health workers play arole in helping and encouraging women of childbearing age to be involved in preventing cervical cancer and thusimproving the life quality of women generally. This study was aimed to determine the relationship between healthworkers’ support and frequency of visual inspection with acetic acid (VIA) for cervical cancer early detectionamong childbearing age women at Pasir Mulya Health Center.Materials and Methods: The study design used was analytical research. Participants in this study were287 childbearing age women who regularly visited Pasir Mulya Health Center. The sampling method used waspurposive sampling. The instrument in this study was questionnaire and the research data was analyzed usingthe Chi-square test.Results: Out of 287 participants, 211 participants (73.5%) received support from the health workers while76 participants (26.5%) did not receive support from the health workers. The number of childbearing age womenwho had done the VIA test was 146 participants, whilst 141 participants never had IVA test previously. A totalof 131 childbearing age women received support and had undergone VIA test. The statistical test obtainedP-value = 0.00.Conclusion: There was significant relationship between health workers’ support and frequency of visual inspectionwith acetic acid (VIA) in childbearing age women at Pasir Mulya Health Center.